2021
DOI: 10.3324/haematol.2021.279196
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the BNT162b mRNA COVID-19 vaccine in patients with chronic lymphocytic leukemia

Abstract: Patients with chronic lymphocytic leukemia (CLL) have a suboptimal humoral response to vaccination. Recently, a BNT162b2 mRNA COVID-19 vaccine was introduced with a high efficacy of 95% in immunocompetent individuals. We investigated the safety and efficacy of BNT162b2 mRNA Covid-19 vaccine in patients with CLL from nine medical centers in Israel, In total 400 patients were included, of which 373 were found to be eligible for the analysis of antibody response. The vaccine appeared to be safe and only grade 1-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
150
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(171 citation statements)
references
References 23 publications
18
150
2
1
Order By: Relevance
“…of cancer patients No. of controls Patients’ age (years) Type of cancer Vaccine type Vaccine scheme Reported outcomes Addeo et al[ 17 ] Switzerland/USA Multicenter, prospective, cohort 244 NA 63 (IQR 55–69) Hematologic malignancy and solid tumor mRNA (BNT162b2/mRNA1273) Incomplete and complete Anti-S IgG Ab, adverse effects, SARS-CoV-2 infection Agha et al[ 41 ] USA Single-center, prospective, cohort 67 NA 71 (IQR 65-77) Hematologic malignancy mRNA (BNT162b2/mRNA1273) Complete Anti-S IgG Ab Barrière et al[ 42 ] France Single-center, prospective, cohort 122 29 69.5 (range 44-90) Solid tumor mRNA (BNT162b2) Incomplete and complete Anti-S IgG Ab, adverse effects Benda et al[ 37 ] Austria Single-center, prospective, cohort 259 NA 65.1 (SD 12.2) Hematologic malignancy and solid tumor mRNA (BNT162b2) Incomplete and complete Anti-S IgG Ab, adverse effects, SARS-CoV-2 infection Benjamini et al[ 53 ] Israel Multi-center, prospective, cohort 373 NA 70 (range 40-89) Hematologic malignancy mRNA (BNT162b2) Complete Anti-S IgG Ab, anti-N IgG Ab, adverse effects Bird et al[ 43 ] UK Single-center, retrospective, cohort 93 NA 67 (IQR 59-73) Hematologic malignancy mRNA (BNT162b2) and viral vector (AZD1222) Incomplete Anti-S IgG Ab Chowdhury et al[ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of cancer patients No. of controls Patients’ age (years) Type of cancer Vaccine type Vaccine scheme Reported outcomes Addeo et al[ 17 ] Switzerland/USA Multicenter, prospective, cohort 244 NA 63 (IQR 55–69) Hematologic malignancy and solid tumor mRNA (BNT162b2/mRNA1273) Incomplete and complete Anti-S IgG Ab, adverse effects, SARS-CoV-2 infection Agha et al[ 41 ] USA Single-center, prospective, cohort 67 NA 71 (IQR 65-77) Hematologic malignancy mRNA (BNT162b2/mRNA1273) Complete Anti-S IgG Ab Barrière et al[ 42 ] France Single-center, prospective, cohort 122 29 69.5 (range 44-90) Solid tumor mRNA (BNT162b2) Incomplete and complete Anti-S IgG Ab, adverse effects Benda et al[ 37 ] Austria Single-center, prospective, cohort 259 NA 65.1 (SD 12.2) Hematologic malignancy and solid tumor mRNA (BNT162b2) Incomplete and complete Anti-S IgG Ab, adverse effects, SARS-CoV-2 infection Benjamini et al[ 53 ] Israel Multi-center, prospective, cohort 373 NA 70 (range 40-89) Hematologic malignancy mRNA (BNT162b2) Complete Anti-S IgG Ab, anti-N IgG Ab, adverse effects Bird et al[ 43 ] UK Single-center, retrospective, cohort 93 NA 67 (IQR 59-73) Hematologic malignancy mRNA (BNT162b2) and viral vector (AZD1222) Incomplete Anti-S IgG Ab Chowdhury et al[ …”
Section: Resultsmentioning
confidence: 99%
“…Of the included 35 studies, 20 reported the seroconversion rate in cancer patients after partial COVID-19 immunization (2574 patients)[ 17 , 20 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , 37 , [42] , [43] , [44] , [47] , [48] , [49] , [50] , [51] , [52] ] and 24 after complete vaccination schemes (4708 patients). [ [17] , [18] , [19] , [20] , 27 , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , 45 , 46 , 48 , 49 , 53 , 54 ] A lower seroconversion rate was achieved by those with incomplete vaccination regimens (51%; 95%CI 41-62) compared to those with fully immunized patients (73%; 95%CI 64-81) ( P =0.0009) ( Figure 2 ).
Figure 2 Rates of seroconversion in patients with cancer according to vaccination regimen.
…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed the literature to gather information on the seroconversion rates after receiving a COVID-19 vaccine in patients with hematologic malignancies. We selected 18 series that provided anti-SARS-CoV-2 spike protein IgG seroconversion rates after full COVID-19 vaccination detailed by hematologic malignancy diagnosis, with at least 20 patients per group (Figure 1 and Supplemental Table 1) (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The literature review also included six additional series that are not included in Figure 1, three due to sampling of serum antibodies before achieving full vaccination as evidenced by lower seroconversions in the healthy control group compared to the rest of the series (20,21), and three that did not provide breakdown of the data according to different histological diagnoses (22,23).…”
Section: Main Textmentioning
confidence: 99%
“…Despite the important caveats resulting from the variability in these series, there are general trends in the data. Patients with chronic lymphocytic leukemia (CLL) have a particularly low rate of seroconversion after COVID-19 vaccination, ranging from 39% to 71% in the reported series (2,(5)(6)(7)(8)(9). A similarly low rate of seroconversion is evident in series reporting on patients with non-Hodgkin lymphoma (NHL), ranging from 42% to 75% (2,4,8,13,14,(16)(17)(18)(19)24).…”
Section: Main Textmentioning
confidence: 99%
“…Study characteristics of the included publications [6][7][8][9][10][11][12][13][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] are summarized in Table 1. Information to assay details of antibody detection and CMI are indicated in Supplementary Appendix, pp.…”
Section: Study Characteristicsmentioning
confidence: 99%